HUBUNGAN HIPEREMESIS GRAVIDARUM TERHADAP MATERNAL ANTENATAL ATTACHMENT DI RS BHAYANGKARA SEMARANG - Indah Wulaningsih; Ira Lindiyani (Jurnal EDUNursing, 2019)
ABSTRACTIntroduction: Maternal and child health is one indicator of achieving Sustainable Development Goals (SDGs). WHO (2016) shows that 585,000 women died during pregnancy and childbirth. Nausea and vomiting (NPV) are common symptoms during early pregnancy, affecting as many as 80% of pregnant women. Studies at Bhayangkara Hospital Semarang shows that in 2017 there were 67 patients experiencing HG, and 2018 there was 1 fetus died from HG, this shows the seriously of the problem of pregnant women who have HG. Purpose: Knowing the relationship of HG to Maternal Antenatal Attachment at Bhayangkara Hospital. Method: Quantitative research method with descriptive correlative design and cross sectional research design. The sample was 32 respondents with inclusion criteria for mothers of pregnant women aged 20-35 years who had HG. Sampling by accidental sampling. The data used questionnaires and analysis of results using chi square. Result: the results of statistical tests using the chi square test, ρ value 0,031 0,668 (≥ 0,005). The result was no significant relationship between hyperemesis gravidarum and maternal antenatal attachment. Keywords : hiperemesis gravidarum, maternal antenatal attachment